STRATEGI PENGEMBANGAN KOMPETENSI DOSEN - Nifasri, Nifasri; Mustaqim, Mustaqim; Suryadi, Rudi Ahmad (Laboratorium Jurusan S1 Manajemen Pendidikan Islam, 2024)
This research aims to analyze the strategies of lecturer’s competency development at STAI al-Azhary Cianjur, as well as to identify the challenges and solutions encountered in this development process. The issues addressed include budget limitations, time constraints, and monitoring systems that affect the effectiveness of the lecturer’s competency development programs. The research method used is a qualitative approach with case study, utilizing data collection techniques such as interviews, observations, and document studies. The data obtained were analyzed descriptively to provide an in-depth overview of the situation faced. The findings indicate that STAI al-Azhary has implemented various competency development programs, such as training, seminars, and research support, which have significantly enhanced the pedagogical and professional abilities of its faculty members. However, challenges regarding budget and time management remain obstacles that need to be addressed. This research also emphasizes the importance of strengthening monitoring and evaluation systems to assess the effectiveness of the programs that have been implemented, allowing administrators to make necessary adjustments. These findings offer insights for higher education administrators to formulate more effective strategies for lecturer’s competency development, aimed at achieving better quality education in the future.